2012
DOI: 10.1107/s0909049512006395
|View full text |Cite
|
Sign up to set email alerts
|

Facilities for macromolecular crystallography at the Helmholtz-Zentrum Berlin

Abstract: Three macromolecular crystallography (MX) beamlines at the HelmholtzZentrum Berlin (HZB) are available for the regional, national and international structural biology user community. The state-of-the-art synchrotron beamlines for MX BL14.1, BL14.2 and BL14.3 are located within the low-section of the BESSY II electron storage ring. All beamlines are fed from a superconducting 7 T wavelength-shifter insertion device. BL14.1 and BL14.2 are energy tunable in the range 5-16 keV, while BL14.3 is a fixed-energy side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
344
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(349 citation statements)
references
References 34 publications
1
344
0
4
Order By: Relevance
“…a part of the physiological substrate histone H3 and human cathepsin L by crystallizing the complex with a catalytic mutant of the enzyme and elucidating its structure [16]. Refinement confirmed the positioning of only three amino acids from the histone H3 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] peptide. Our crystal packing analysis suggested that there is not enough space to accommodate all 14 peptide residues in the available space in the active site cleft.…”
Section: Abstract: Cathepsin; Cysteine Cathepsin; Substrate Interactionmentioning
confidence: 99%
“…a part of the physiological substrate histone H3 and human cathepsin L by crystallizing the complex with a catalytic mutant of the enzyme and elucidating its structure [16]. Refinement confirmed the positioning of only three amino acids from the histone H3 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] peptide. Our crystal packing analysis suggested that there is not enough space to accommodate all 14 peptide residues in the available space in the active site cleft.…”
Section: Abstract: Cathepsin; Cysteine Cathepsin; Substrate Interactionmentioning
confidence: 99%
“…Data collection, structure determination and refinement. Diffraction data were collected on BL14.1 operated by the Helmholtz-Zentrum Berlin (HZB) at the BESSY II electron storage ring (Berlin-Adlershof, Germany) 23 at wavelengths of 1.0727 or 0.9184 Å, respectively. Data were processed with the program XDSAPP 24 .…”
Section: Methodsmentioning
confidence: 99%
“…and M.G., manuscript in preparation) were soaked in cryosolution containing 10 mM magnesium chloride or 50 mM zinc chloride, respectively, for 1 h before freezing. Diffraction data sets were collected at the MX beamline BL14.1 at the BESSY II electron storage ring (Berlin-Adlershof, Germany) operated by the Helmholtz-Zentrum Berlin 43 , with a MX-225 CCD detector (Rayonix, Evanston, USA). Data sets were collected at 100 K and a wavelength of 0.918 Å (crystal form 1 and 2) or 1.283 Å (Zn-soak) over 200°(crystal form 1, Zn-soak) or 130°(crystal form 2) with 1°(crystal form 1 and 2) or 0.5°(Zn-soak) rotation per frame.…”
Section: Methodsmentioning
confidence: 99%